GRADING SCALE OF LUMBAR DEGENERATIVE DISEASE IN FULL SPINE X-RAY - Vasconcelos,Iúri Tomaz de (2019)
ABSTRACT Objective: To present a new lumbar degenerative disease grading scale considering full spine radiography and to evaluate its inter- and intraobserver reproducibility. Methods: A total of 132 full spine radiographies in the anterior and lateral views were analyzed. The cases were independently graded by two examiners. The radiographic parameters observed were osteophytosis, loss of disc height, sclerosis and subchondral cysts, number of affected segments, deformities, and signs of instability. The grading scale was proposed as follows: Degree zero corresponded to the absence of signs of degenerative disease in the lumbar spine; Grade I – presence of signs of degenerative disease up to two segments; Grade II – involvement of three or more segments; Grade III – associated deformity or signs of instability. The intra- and interobserver reproducibility was determined by the Kappa coefficient (κ) in general and according to the age group. Results: Kappa coefficient obtained for interobserver and intraobserver analysis showed excellent overall correlation (0.855 and 0.902, respectively). When analyzed according to age, results obtained in intraobserver correlation remained excellent (κ >0.8) in all age groups. The interobserver correlation remained excellent, except in the age range of 40-59 years (κ = 0.773), although maintaining a substantial reproducibility. Conclusion: The grading scale of lumbar degenerative disease observed in full spine x-rays showed excellent inter- and intraobserver reproducibility. Level of Evidence I; Diagnostic study.